The impact of cultural diversity in a polarised society: a study Bessie Head's maru, Phaswane Mpe's welcome to our hilbrow and Paul Freeman's rumours of ophir - Chimwaza, Gamuchira (Midlands State University, 2014)
This literary study investigates the effects and role of cultural diversity in influencing inter- cultural relations and people’s individual relations in society. It uses the textual analysis which plays a very important role in the research findings. The study analyses Phaswane Mpe’s Welcome to Our Hilbrow (2001), Paul Freeman’s Rumours Of Ophir(1998) and Bessie Head’s Maru(1971).The exploration of how cultural diversity influences inter-cultural relations in society is substantiated through Hofetsd’s (1984) cultural dimensions theory and Kallen’s(1910) cultural pluralism theory. The study established that ethnic and racial stereotypes are instilled at a tender age and that coexistence is necessary if cultural diversity is to have a more positive impact in a polarised society. This research also established that most of the impacts associated with cultural diversity in a polarised society are rather negative than positive.